(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Identification of an efficient parameter of voice for forensic investigation is a challenging task. The process of speech investigation includes examination of the speech profile which helps in the recognizing the suspect. The fundamental frequency, pitch, intensity, jitter, shimmer, MPD, and HNR have been evaluated in persons with the habitual voice stressful environmental condition that is the prolonged tobacco usage from 5 to 50 years, and it was compared with nontobacco users’ voice. It was observed that fundamental frequency, minimum and maximum pitch, jitter and shimmer were least varying under prolonged exposure of tobacco consumption.